Peran Social Networking Sites dalam meningkatkan Stakeholder Engagement: A Literature Review - Falah Muthiah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
The role of Social Networking Sites in ongoing communication becomes easier, especially to build stakeholder management and stakeholder engagement, provide information, and monitor information to manage the image and reputation of the company. This literature review aims to explore the role of Social Networking Sites in increasing stakeholder engagement. This research method is a literature review that uses journal reference sources sorted by the role of Social Network Sites in increasing Stakeholder Engagement. The results show that Social Network Sites on the platforms Facebook, Instagram, Twitter, and Youtube are tools to increase engagement with internal and external stakeholders to create relationships and improve the company's image and reputation. Social Network Sites play a role in building connections, relational relationships between customers, assessing the matrix for stakeholders, assessing company performance, assessing stakeholder participation, assessing marketing strategies, building relationship relationships, and forming customer loyalty. Online activities carried out by stakeholders are related to the image of the company's reputation, so that digital public relations and corporate communications must adequately manage it.